2022
DOI: 10.3390/gels8070429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat-Moisture Treatment on the Physicochemical Properties and Starch Digestibility of Mix Powder (Wheat Flour-Black Soybean Flour) and Corresponding Cookies

Abstract: In order to improve the nutritional value and reduce starch the digestibility of black soybean cookies, superfine black soybean flour was modified by heat-moisture treatment (HMT). The physicochemical properties, structure analysis of the flour samples and corresponding dough, and nutritional, physical, and textural properties of the cookies were investigated. After HMT, the water and lactic acid retention capacity and the oil binding capacity of mix powder dramatically increased, being almost twice the value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…It was observed that HMT altered nutrition characteristics in cassava, in agreement with previous findings identifying characteristic nutritional changes in different starch sources after HMT [21]. Yang et al [22] reported that HMT lowered moisture, crude fiber, ash, crude protein, and crude fat levels. This finding was in contrast with our findings of decreased OM and increased crude protein and fat content by HMT=Heat-moisture treatment, HMT0=Without heat-moisture treatment (control), HMT1=One cycle of heat-moisture treatment, HMT2=Two cycles of heat-moisture treatment, HMT3=Three cycles of heat-moisture treatment, SEM=standard error of mean, B=Maximum gas production, k=Rate of gas production, L=Lag time, h=Hour, and superscript differences on the same line indicate significant differences (p < 0.05) HMT.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was observed that HMT altered nutrition characteristics in cassava, in agreement with previous findings identifying characteristic nutritional changes in different starch sources after HMT [21]. Yang et al [22] reported that HMT lowered moisture, crude fiber, ash, crude protein, and crude fat levels. This finding was in contrast with our findings of decreased OM and increased crude protein and fat content by HMT=Heat-moisture treatment, HMT0=Without heat-moisture treatment (control), HMT1=One cycle of heat-moisture treatment, HMT2=Two cycles of heat-moisture treatment, HMT3=Three cycles of heat-moisture treatment, SEM=standard error of mean, B=Maximum gas production, k=Rate of gas production, L=Lag time, h=Hour, and superscript differences on the same line indicate significant differences (p < 0.05) HMT.…”
Section: Discussionsupporting
confidence: 88%
“…Yang et al . [ 22 ] reported that HMT lowered moisture, crude fiber, ash, crude protein, and crude fat levels. This finding was in contrast with our findings of decreased OM and increased crude protein and fat content by HMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly baked potatoes were allowed to cool for about 2 h and then cut into small square pieces. After that, the samples were mounted onto the sputter coater to sputter-coat the samples with a thin layer of platinum (Pt) under vacuum . Lastly, the Pt-coated samples were attached to double-sided carbon tape mounted on an aluminum stub and placed into the SEM microscope .…”
Section: Methodsmentioning
confidence: 99%
“…After that, the samples were mounted onto the sputter coater to sputter-coat the samples with a thin layer of platinum (Pt) under vacuum. 27 Lastly, the Pt-coated samples were attached to double-sided carbon tape mounted on an aluminum stub and placed into the SEM microscope. 28 The cookie samples were then observed under two magnification levels of 50× and 100×.…”
Section: Confocal Laser Scanning Microscopy (Clsm) Of Doughmentioning
confidence: 99%